A framework for the design of courses and the integration of those courses into a curriculum - O'Donovan, Brian (My University, 1994)
Designers of both computerised information systems and instructional systems are faced with a need to find more effective methods of identifying and supplying the information that the users of these systems require. It is suggested that a transfer of selected information systems methodologies to instructional design would be of benefit. An entity relationship diagram is drawn up for a simple course and once "decomenced" and set up in orthogonal form is shown to be a useful tool for setting objectives, establishing modules and the learning sequence and listing topics. (Abbreviation abstract)
A technical report submitted to the Faculty of Commerce, University of Witwatersrand., In partial fulfilment of the degree of Master of Commerce
Keywords: Accounting -- Study and teaching.; Information technology.